2018
DOI: 10.1038/s41598-018-33609-2
|View full text |Cite|
|
Sign up to set email alerts
|

Near-absolute polarization insensitivity in graphene based ultra-narrowband perfect visible light absorber

Abstract: Strong light-graphene interaction is essential for the integration of graphene to nanophotonic and optoelectronic devices. The plasmonic response of graphene in terahertz and mid-infrared regions enhances this interaction, and other resonance mechanisms can be adopted in near-infrared and visible ranges to achieve perfect light absorption. However, obtaining near-absolute polarization insensitivity with ultra-narrow absorption bandwidth in the visible and near-infrared regimes remains a challenge. In this rega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 76 publications
0
21
0
Order By: Relevance
“…Infinite‐fold symmetric designs, such as nanoshperes, nanodiscs, and nanopillars, can be used to mitigate this deficiency . It is worth to note that proper arrangement of particles can also provide this polarization insensitivity, even for elongated asymmetric design units . Lank et al demonstrated a strong light absorption using Si nanopillars .…”
Section: Light Trapping Schemesmentioning
confidence: 99%
See 1 more Smart Citation
“…Infinite‐fold symmetric designs, such as nanoshperes, nanodiscs, and nanopillars, can be used to mitigate this deficiency . It is worth to note that proper arrangement of particles can also provide this polarization insensitivity, even for elongated asymmetric design units . Lank et al demonstrated a strong light absorption using Si nanopillars .…”
Section: Light Trapping Schemesmentioning
confidence: 99%
“…This is important for the practical application of this strategy considering the fact that the incident solar irradiation is also unpolarized. Besides these symmetric designs, the polarization insensitivity can be acquired by arrangement of gratings in a proper way . A recent study proposed a metamaterial based mirror based on periodic patterns of Ag nanoparticles on Ag film .…”
Section: Light Trapping Schemesmentioning
confidence: 99%
“…Graphene is a representative metallic layered material consisting of carbon atoms arranged in a hexagonal lattice with strong inplane chemical bonds 12 14 . Although graphene has high electron concentration, weak light absorption and fast carrier recombination limit its application in optoelectronics 15 , 16 . PbS colloidal quantum dots (QDs) are promising semiconductors for application as active material in near-infrared optoelectronics because of their small and tunable direct band gap 17 , 18 .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the broadband absorbers, some studies aim to design narrowband absorbers that have an absorbance peak at single resonance wavelength. Many different nanopattern configurations were employed for achieving narrowband absorbers that are highly sensitive to the changes in the dielectric properties of their surroundings . Liu et al designed an MIM nanodisk narrowband perfect absorber with a sensitivity of 400 nm RIU −1 (refractive index unit) .…”
Section: Introductionmentioning
confidence: 99%